The Importance and Approaches to Islamic Education Planning in the Development of an Effective Education System - Ridho, Muhammad (Yayasan Pendidikan Tanggui Baimbaian, 2026)
Islamic educational planning has an important role in directing how the education system is managed so that set goals can be met successfully, smoothly, and in a lasting way. This study examines the basic concepts, urgency, objectives, benefits, and various approaches in Islamic educational planning. Using a literature review method, this research looks at different related literature and analyzes it through content analysis to identify patterns of thought and the frameworks of approaches used. The result show that Islamic education planning is a structured approach to setting up educational policies, priorities and strategies while taking into account social situations, economic factors and community requirement. Several approaches that can be applied include the social needs approach, the labor market approach, the cost-benefit approach, the cost-effectiveness approach, the systems approach, and the integrated approach. Comprehensive and contextual planning is anticipated to enhance the quality of Islamic education while creating graduates who are intellectually advanced, able to adjust to change and of good character.